Upconversion properties of Er, Yb co-doped KBi(MoO4)2 nanomaterials for optical thermometry. Issue 12 (15th June 2023) - Samal, Satish Kumar; Pushpendra; Yadav, Jyoti; Naidu, Boddu S.
Abstract: Rare earth ions doped upconversion materials have an extensive range of utilizations because of their exceptional luminescence properties. Here, scheelite type Yb 3+, Er 3+ co-doped KBi(MoO4 )2 nanomaterials were produced by means of a conventional co-precipitation method at room temperature with a typical crystallite size of 13 nm. 980 nm excitation aided in the investigation of the concentration and power-dependent upconversion emission. The optimum upconversion emission is obtained with Er and Yb concentrations of 0.035 and 0.125 mol%, respectively in KBi(MoO4 )2 nanomaterials. The intensity ratio of upconversion emission bands based on 529 and 551 nm is investigated in the temperature range of 200–550 K and the theoretical function is used for fitting the exploratory information. The absolute sensitivity is found to be of maximum value of 0.0123 K -1, indicating that this double molybdate can be utilized as a potential probe for luminescence-based temperature sensing.